Interaction of the A1 Subunit of Factor VIIIa and the Serine Protease Domain of Factor X Identified by Zero-length Cross-linking - Lapan, Kirsty A.; Fay, Philip J. (Thrombosis and Haemostasis, 1998)
We have previously used a solid phase binding assay to localize a Factor X (FX) interactive site to the acidic C-terminus of the A1 subunit of FVIIIa (Lapan KA, Fay PJ. J Biol Chem 1997; 272: 2082-2088). The complex of FVIII-FX was made covalent following reaction with the zero-length cross-linking reagent 1-ethyl-3-(3-dimethylaminopropyl-)carbodiimide hydrochloride (EDC). Western blotting of the thrombin-cleaved complex showed that the A1 subunit of FVIIIa associated with FX heavy chain. The FX-A1 product was also detected following cross-linking to the A1/A3-C1-C2 dimer, but not the activated protein C-cleaved A1336/A3-C1-C2 form, indicating that a residue(s) in the region spanning Met337-Arg372 contributed to the intermolecular ion pair(s). A synthetic peptide to this acidic region (FVIII337-372) cross-linked to FX and the product was alkaline resistant indicating that amide linkage(s) were formed. Sequence analysis of the FX-FVIII337-372 adduct suggested that the first 12 NH2-terminal residues of the FX and peptide do not participate in cross-link formation. Conversion of the cross-linked product to FXa by RVV-X showed that the peptide was associated with the serine protease-forming domain of the heavy chain. These results indicate that the association of FVIIIa and FX occurs from a salt linkage(s) formed between residues of the A1 acidic C-terminus of the cofactor (within residues 349-372) and the serine protease-forming domain of the substrate.